The Role of Leaders in the Development of Successful Corporate Strategy - Suharto , Suharto (SEAN Institute, 2023)
Rapid changes in the business environment demand adaptive and innovative strategies to ensure company sustainability and growth. This research will focus on how leaders can be the main catalyst in formulating, implementing and evaluating effective company strategies. This research uses a qualitative approach with descriptive methods. This research produces a deep understanding of the crucial role of leaders in the development of successful corporate strategies. The findings show that leaders play a role in formulating the vision and mission, analyzing the external environment, identifying opportunities and challenges, building a supportive organizational culture, communicating and implementing strategic plans, carrying out continuous monitoring and evaluation, and developing teams and capabilities. In this context, leaders are not only strategic decision makers, but also agents of change, motivators and shapers of organizational culture. In conclusion, effective leaders have an irreplaceable role in directing an organization towards achieving its strategic goals.